Analisis Makna Pesan Kata Genji Pada Film Crows Zero - Muhammad Nur Zikirullah; Taufiq Furqon Nurhakim (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Film plays a significant role in shaping perceptions and behaviors, particularly among adolescents. Action films with themes of teenage life and inter-gang fights, such as Crows Zero, are compelling to watch and have the potential to be a source of inspiration. This study aims to analyze the meaning of the messages contained in the film Crows Zero, focusing on understanding that the name "Genji" is not just the main character's identity but also holds a deep symbolic meaning. Employing a qualitative approach with semiotic analysis, this research seeks to describe, analyze, and record the meanings and symbols present in the film. The findings indicate that despite depicting violence, Crows Zero conveys moral messages about true strength, the importance of self-discovery, the value of friendship, and perseverance. The character of Genji has a significant influence on the audience, especially teenagers, who emulate his speech and behavior as a source of motivation and inspiration. Overall, the name "Genji" in the film represents leadership, spirit, and the search for identity, which are highly relevant to adolescent life, while also demonstrating the effectiveness of film as a tool for conveying messages and shaping the audience's character..